Proceso de atención de enfermería en paciente con apendicitis. - Macías Zambrano, Deyanira Francelly (2021)
Appendeptomy is considered to be the most common surgical intervention worldwide. The following case study will present the medical history of a 34-year-old male patient presenting 24-hour clinical picture due to abdominal pain at the level of the epigastrium irrigated to the right iliac fossa, which decided to perform surgery. realziation of the clinical case is the application of the Nursing Care Process in a patient diagnosed with appendicitis where the most prevalent health problems in the patient were identified, the explanation in the theoretical framework indicates that the symptoms of this disease are very varied which that by means of images allow to diagnose the disease with confidence. During hospital admission, care plans were drawn up that detailed the Nursing Diagnoses that were related to the patient's signs and symptoms, through a planning of the possible results, the interventions that guided the recovery of the patient were determined along with the medical treatment. In conclusion, the continuous study of this disease and the systematic observation of the patient allowed the development of the nursing process that contributed to providing quality care and warmth, promoting patient comfort.